Public Perception Of Spiritual Guidance In Malaysian Worship-Friendly Hospitals - Adlina Ramzan; Abdur Razzaq; Neni Noviza (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze the perception of the people of Gombak, Malaysia towards spiritual guidance at Persra Ibadah Hospital. The background of the research departs from the importance of spiritual services in supporting the patient's healing process, along with a holistic approach that includes physical, psychological, social, and spiritual dimensions. The research method used is qualitative with a descriptive approach, involving interviews and observations of the Gombak community. The results of the study show that the majority of people have a positive perception of spiritual guidance, because it is considered to be able to provide inner peace, spiritual motivation, and help patients in carrying out worship when sick. However, some people also consider that socialization and promotion regarding the role of spiritual guidance is still not optimal. This study concludes that spiritual guidance at Persra Ibadah Hospital needs to be strengthened through the development of more systematic programs and the dissemination of information to the community.